DEMOGRAPHIC PROFILE OF PENAN STUDENTS IN TWO PUBLIC SECONDARY SCHOOLS AND ACADEMIC ATTAINMENT OF THEIR SCHOOL LEAVERS - Juna, Liau (Institute of Borneo Studies, UNIMAS, 2020)
This article documents the demographic background of Penan secondary school students that are studying in two public secondary schools located at the Baram District in Miri Division, Sarawak Malaysia and the academic achievement of their schools’ leavers. Ethnographic research methods which include survey questionnaire, interviews and field observations are used to obtain the data. Data from interviews and observations areanalysedthematically and Microsoft Excel is used toanalysedata related to demographic profile of students such as their age, gender, village and level of education. Data on the cost of transport used to go to boarding schools and information related to the access to the internet and telephone service are analysed to examine students’ mobility and accessibility. Access to social services, including the internet and telephone, is important for all people, including Penan populations. In the context of education, internet access allows for learning to take place at any time, any place and at any pace. Through the data on students’ demographic profile and academic achievement of school leavers, the study calls for the understanding of Penan education beyond individuals’ agency. This includes the understanding of students’ mobility from village to boarding schools which interlinked with the idea that education enables and promotes the acquisition of skills, knowledge and broadens individuals’ horizons. Moreover, pursuing secondary schools outside students’ villages provides opportunities for employment outside their villages after the completion of their SPM or STPM examinations; opens a window to advance their education to tertiary level as an attempt to improve their socio-economic status.